2000
DOI: 10.1177/003693300004500109
|View full text |Cite
|
Sign up to set email alerts
|

What Stops Effective Clinical Audit? Reports from the Front Line

Abstract: Semi-structured interview were conducted with 145 clinicians from a variety of clinical backgrounds in twelve Trusts across three Scottish health boards. Questions examined barriers to the audit process and obstacles that impeded the implementation of changes in response to the audit findings as well as the need for resources to facilitate the audit activity. The most difficult part of the audit process was reported as data collection (32%) but almost half of respondents would have changed the way the audit wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This represents a real challenge in itself. Obstacles to implementing MDRs or clinical audit are well known . In Cameroon, assuming the training will be adequate, two main obstacles remain: the lack of local resources to correct the problems identified through MDRs and the perceived lack of potential benefit for the healthcare providers in implementing MDRs (increased workload, relationship problems).…”
Section: Challengesmentioning
confidence: 99%
“…This represents a real challenge in itself. Obstacles to implementing MDRs or clinical audit are well known . In Cameroon, assuming the training will be adequate, two main obstacles remain: the lack of local resources to correct the problems identified through MDRs and the perceived lack of potential benefit for the healthcare providers in implementing MDRs (increased workload, relationship problems).…”
Section: Challengesmentioning
confidence: 99%
“…The biggest obstacle to making changes resulting from MDR and near-miss case reviews is colleagues' attitude and lack of support from facility managers [10][11][12]. Health professionals have to be aware of these obstacles but should also be encouraged by the successful experiences documented in Malawi [13] and Senegal [8,14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that clinical audit projects often fail to complete the loop and become a waste of resources (Gnanalingham et al, 2001). Furthermore, other studies demonstrate that there are significant barriers to the clinical effectiveness process (Johnston et al, 2000). One such barrier may be the constant movement of junior doctors as they embark on rotational training.…”
Section: Discussionmentioning
confidence: 99%